2011
DOI: 10.1118/1.3556559
|View full text |Cite
|
Sign up to set email alerts
|

Minimax optimization for handling range and setup uncertainties in proton therapy

Abstract: Purpose: Intensity modulated proton therapy (IMPT) is sensitive to errors, mainly due to high density dependency and steep beam dose gradients. Conventional margins are often insufficient to ensure robustness of the plans. In this paper, a method is developed that takes the uncertainties into account during the plan optimization. Methods: Dose contributions for a number of range and setup errors are calculated and a minimax optimization is performed. The minimax optimization aims at minimizing the penalty of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
415
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 391 publications
(417 citation statements)
references
References 36 publications
2
415
0
Order By: Relevance
“…The minimax method does not minimize the worst of all possible scenarios, but the worst scenario within some predefined range. It considers only scenarios that are physically reliable; with unnecessary conservative case scenarios being avoided 3, 4. The range of patient setup error specified by the user was 0.5 cm in LR, 1.0 cm in IS, and 0.5 cm in AP direction for this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The minimax method does not minimize the worst of all possible scenarios, but the worst scenario within some predefined range. It considers only scenarios that are physically reliable; with unnecessary conservative case scenarios being avoided 3, 4. The range of patient setup error specified by the user was 0.5 cm in LR, 1.0 cm in IS, and 0.5 cm in AP direction for this study.…”
Section: Methodsmentioning
confidence: 99%
“…Position uncertainties come from two sources: tumor motion and variations in tumor shapes, and patient setup uncertainties. One way to approach these uncertainties is to use minimax optimization 3. Instead of expanding the internal target volume (ITV) with a fixed margin to create the planning target volume (PTV), robust optimization allows entering the setup uncertainties into the planning computer and discretizes them into multiple scenarios (shifts within the margin bounds).…”
Section: Introductionmentioning
confidence: 99%
“…The RayStation system offers minimax optimization, in which the optimization functions selected to be robust are considered under the worst‐case scenario 8. The interfractional patient‐setup uncertainties are considered to be random; they are incorporated by shifting the isocenter of the patient in the anterior‐posterior (A‐P), superior‐inferior (S‐I), and right‐left (R‐L) directions by the same margin as those used for defining the PTV.…”
Section: Methodsmentioning
confidence: 99%
“…In proton therapy, setup errors, density errors, and organ motion can lead to differences in dose distributions when comparing the planned and delivered doses. Several authors have previously reported that stochastic programming and robust optimization in IMPT have minimized this problem 5, 6, 7, 8, 9, 10, 11, 12. Presently, RayStation (RaySearch Medical Laboratories AB, Stockholm, Sweden) offers one of the robust optimization methods used to address these demands.…”
Section: Introductionmentioning
confidence: 99%
“…This ensures a minimum level of plan quality, but results in a dependence on limitations of uncertainty and the potential for the system to over optimize low probability scenarios at the cost of plan quality of higher probability scenarios. In a paper by Fredriksson,53 in which the formalism was introduced, the method was shown to provide robust plans with increased lung sparing over PTV expansions for intensity modulated proton therapy, whilst work by Byrne et al45 has demonstrated its potential in IMRT planning. The implementation of min‐max optimization by the vendor is provided in two options; specified 3‐dimensional offsets set by the user or planning over a range of patient scans (Fig.…”
Section: Introductionmentioning
confidence: 99%